Narcissistic susceptibility to conspiracy beliefs exaggerated by education, reduced by cognitive reflection - Cosgrove, Tylor J.; Murphy, Christopher P. (Frontiers in Psychology, 2023)
Conspiracy theories are alternate viewpoints of provided explanations; sensational stories revolving around small groups exerting control for nefarious reasons. Recent events and research have outlined myriad negative social and personal outcomes for those who endorse them. Prior research suggests several predictors of susceptibility to conspiracy theories, including narcissistic personality traits (grandiosity, need for uniqueness), cognitive processes (critical thinking, confirmation bias) and lack of education. The aim of the current paper was to explore how facets of narcissism predict susceptibility to conspiracy theories. It was expected that narcissism would be a positive predictor, but education and cognitive reflection would act as protective factors, reducing this effect. Study one utilized an international survey (N = 323) to investigate the role of education as a protective tool in the relationship between narcissistic traits and conspiratorial beliefs. Support was found for the hypotheses that individuals with higher levels of grandiosity, vulnerable narcissism, a strive for uniqueness, and a strive for supremacy predicted higher levels of conspiracy endorsement. Higher education and STEM education were associated with lower levels of conspiracy endorsement, however all significant moderations indicated that for narcissistic individuals, education increased their likelihood of adopting conspiracy beliefs, contrary to expectation. To investigate this further, study two analyzed a large-scale publicly available dataset (N = 51,404) to assess the relationship between narcissism, critical thinking skills (specifically cognitive reflection) and conspiracy beliefs pertaining to the COVID-19 pandemic. As expected, analysis found narcissism and poor cognitive reflection (intuitive thinking) as predictors of conspiracy beliefs. Higher levels of cognitive reflection were found to be protective, moderating and reducing the impact of narcissism on endorsement of conspiracy theories. The findings suggest that cognitive reflection, but not education protect against narcissistic conspiracy belief. Moreover, that cognitive reflection may have a lessened effect against conspiracy theories adopted for social or ideological reasons. These findings improve understanding of both the role and limitations of education/critical thinking skills as protective factors against conspiracy theory endorsement.